(untitled) (Economics and region, 2022)
Due to modern conditions, the importance of implementing a project approach in the management processes of local self-government bodies is growing, which will allow not only to facilitate a quick response to legislative changes, but also to effectively form and implement a territorial community development strategy. Local governments tend to run several projects simultaneously, so project portfolio management is a key competency for flexible adaptation to environmental changes. Since project activity is carried out under conditions of uncertainty, knowledge of the basics of project management is necessary in the professional activity of public managers. In this regard, a review of existing approaches to project management in local self-government is quite relevant and necessary in modern conditions. The topic of project management research in local self-government is studied by a small number of scientists. In this context, the author sets a task – to analyze approaches to project management in local self-government. In the process of research, it was established that the use of projects in local self-government as a tool for implementing strategic goals for the development of territorial communities allows to attract additional resources and implement a number of projects for the implementation of strategic initiatives, however, the project activities of local self-government bodies cannot be considered effective or fully meet the requirements of today. It was found that the basis of the construction of the project and program management system in foreign countries are international and national management standards, which summarize the experience of developed countries accumulated in the development and implementation of projects and programs. It was found that the most common models for assessing the maturity of organizational projects in international practice are the project management maturity model (PMMM/PM3), the organizational project management maturity model (OPMMM/OPM3), the portfolio, program and project management maturity model (P3M3), the IPMA Delta® Model ( Project Excellence Model). We suggest that local self-government bodies give preference to project methodologies that have shown their effectiveness and efficiency, primarily PRINCE2, Scrum, Agile and MSP. It was determined that one of the fundamental trends is the transition from traditional project management practices to project cycle management in local self-government. It has been found that in order to ensure the effective achievement of the goals of projects and programs during their development and implementation, the project cycle management methodology based on integrated and logical-structural approaches is used. It has been established that there is a worldwide trend of transition from the management of individual projects to the management of a portfolio of projects or a program. It was determined that the management of the portfolio of projects (programs) for the implementation of large-scale projects of state importance provides the following opportunities: to direct limited resources to projects that are most important for achieving the goals of socio-economic development of the city, region, and country; to analyze indicators of efficiency and cost of projects throughout the entire life cycle in order to make a decision on introducing new projects into the portfolio or closing unprofitable and inefficient projects; identify and delete unpromising and duplicate projects. Conclusions and suggestions developed by the author and proposed in the article can be used for: application of theoretical knowledge about project management in local self-government. A promising direction of further research on this issue is ways of improving the methodological and practical activities of state and non-governmental structures, as well as all interested parties involved in project management, which represents both scientific and applied value, and the development of optimal methods that will allow in a short time and with minimal costs, introduce a specific methodology for risk assessment in the project management of local self-government bodies.